2021
DOI: 10.1021/acs.inorgchem.1c02929
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Localization Studies of the Luminescent Analogue of an Anticancer Ruthenium Iminophosphorane with High Efficacy in a Triple-Negative Breast Cancer Mouse Model

Abstract: The potential of ruthenium­(II) compounds as an alternative to platinum-based clinical anticancer agents has been unveiled after extensive research for over 2 decades. As opposed to cisplatin, ruthenium­(II) compounds have distinct mechanisms of action that do not rely solely on interactions with DNA. In a previous report from our group, we described the synthesis, characterization, and biological evaluation of a cationic, water-soluble, organometallic ruthenium­(II) iminophosphorane (IM) complex of p-cymene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 66 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…In addition, BODIPY can participate in the formation of self‐assembled systems such as metal‐based compounds for disease treatment and intracellular localization studies of analytes, which will shed light on the development of novel multifunctional theranostic agents. Based on their previous report of the organometallic ruthenium(II) iminophosphorane complex of p ‐cymene, [ 323 ] Contel and co‐workers [ 324 ] developed two luminescent analogs containing BODIPY moiety in the iminophosphorane scaffold. Fluorescent BODIPY moiety allows the distribution of these ruthenium complexes within biological tissues to be visualized.…”
Section: Main Specific Biomedical Applications Of Bodipymentioning
confidence: 99%
“…In addition, BODIPY can participate in the formation of self‐assembled systems such as metal‐based compounds for disease treatment and intracellular localization studies of analytes, which will shed light on the development of novel multifunctional theranostic agents. Based on their previous report of the organometallic ruthenium(II) iminophosphorane complex of p ‐cymene, [ 323 ] Contel and co‐workers [ 324 ] developed two luminescent analogs containing BODIPY moiety in the iminophosphorane scaffold. Fluorescent BODIPY moiety allows the distribution of these ruthenium complexes within biological tissues to be visualized.…”
Section: Main Specific Biomedical Applications Of Bodipymentioning
confidence: 99%
“…The live-cell confocal images were taken using blue channels (λ ex = 405 nm, λ em = 420−470 nm) for complexes and a red channel (λ ex = 635 nm, λ em = 650−740 nm) for MTDR. 86 The microscope was operated with Leica LAS-X software. The colocalization analyses were performed with ImageJ software.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Miachin et al developed two luminescent derivatives of their triple-negative breast-canceractive ruthenium(II) piano stool complex; they reported that the addition of a fluorophore changed the biological characteristics of the resulting complexes (Figure 6: RU7). They found that the cytotoxicity was reduced from 2.72 ± 0.11 to 68.23 ± 8.2 in MDA-MB-231 cells, and ICPMS experiments found that the complexes also varied in their cell localization and uptake [58]. Although these findings justify the conclusion that adding a fluorophore can still be used to build a more complete picture of cellular accumulation and mechanism as reported, it is clear that developing a cytotoxic agent with inherent fluorescence would be more beneficial.…”
Section: Piano Stool Complexesmentioning
confidence: 99%